Kissing the gunner's daughter eaudiobook Inspector wexford mysteries series, book 15. - Rendell, Ruth (Chief Inspector Wexford Mystery, 2019)
Wexford is horrified by the carnage he encounters at Tancred Manor, home of a famous anthropologist, but he is determined to do all that he can for 17-year-old Daisy, the only survivor of the mass murders that obliterated her family.